Influence of impairment type on the development of competitive athletes with a physical disability - Allan, V.; Dehghansai, N.; Pinder, R. A.; Baker, J. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
The developmental trajectories of athletes with physical disabilities are complex —and when it comes to understanding the factors that influence their development in sport, existing research has only scratched the surface. To deepen our understanding, this study examined the influence of impairment type on (a) how athletes were introduced to sport, (b) the age at which nine sport-related developmental milestones (e.g., first participated in offseason training) were achieved, and (c) the time it took to reach each milestone. An international sample of competitive athletes with physical impairments (N = 187; 68% male; Mage = 33) provided training histories using the Developmental History of Athletes Questionnaire. Participants were divided into four groups: spinal cord injuries (SCI; n = 67), amputations and/or limb deficiencies (A/LD; n = 48), cerebral palsy and/or spina bifida (CP/SB; n = 32), and other physical impairments (OPI; n = 40). Participants with SCI were most frequently introduced to sport throughhealthcare professionals (54%), A/LD through friends or relatives (26%), and CP/SB through talent search programs (22%). Separate one-way ANOVAs revealed that the SCI group was significantly older than the other three groups at eight of the nine milestones (p < .05). However, significant differences persisted for only three milestones in terms of time. Specifically, participants with SCI took significantly less time than participants with OPI to reach these three milestones (p < .01). Thus, despite differences in age and how they got involved, athletes with distinct physical impairments appear to progress through sport at a similar rate.